Pengaruh Beberapa Pupuk Kandang dan Volume Tanam Terhadap Pertumbuhan dan Hasil Tanaman Sawi Hijau (Brassica juncea L.) Varietas Tosakan pada Sistem Vertikultur - Rima Febryani; Darso Sugiono; Winda Rianti (Jurnal Ilmiah Wahana Pendidikan, 2022)
The use of manure fertilizer and volume of crops with vertical system can be an option to increase the productivity of Indian mustard (Brassica juncea L.). The purpose of this study was to determine and obtain the best results from the treatment of several manure fertilizers and planting volume on the growth and yield of Indian mustard (B. juncea L.) Tosakan variety in a verticulture system. The study was conducted at a screen house, Purwakarta Regency, West Java. The experiment was carried out from June 2022 to July 2022. The method used in this study was experimental method with a single factor randomized block design (RBD) with 12 combinations treatment and was repeated 3 times, so that 36 experimental units were obtained. Manure fertilizer and planting volume gave a significant result on B. juncea in verticultural system. The highest yield was achieved by treatment L (Soil + Chicken Manure with a volume of 25 kg) with a ratio (1:1) which resulted in plant height 34.92 cm, leaf area 392.50 cm2, root length 20.83 cm, fresh weight per plant 100.67 grams, and fresh weight per gutter is 853.33 grams.